RESEARCH PAPER ON THE ROLE OF LAW SCHOOLS IN ACHIEVING SDG5 GENDER EQUALITY - Goswami, Shreya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Sustainable Development Goals (SDGs) adopted by the United Nations in 2015 represent a global blueprint for peace and prosperity for people and the planet. SDG5, which aims to "Achieve gender equality and empower all women and girls", is a critical component of this ambitious agenda. Ensuring gender equality is not only a fundamental human right, but also a necessary foundation for a peaceful, prosperous and sustainable world. Law schools have a pivotal role to play in advancing SDG5 and promoting gender equality. As institutions that train future legal professionals, law schools have a responsibility to embed principles of gender equality and equity throughout their curricula, policies and practices. By doing so, they can cultivate a new generation of lawyers, judges, policymakers and leaders who are equipped to champion gender equality and drive transformative change. This research paper examines the multifaceted ways in which law schools can contribute to the achievement of SDG5. It explores key strategies and best practices that law schools can implement to promote gender equality, empower women and girls, and dismantle the systemic barriers that perpetuate gender-based discrimination and violence.